2019
DOI: 10.1101/555490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic and Gene Regulatory Mechanisms in Schizophrenia, Autism, and 22q11.2 CNV Mediated Risk for Neuropsychiatric Disorders

Abstract: Word Count: 244 Main Text Word Count: 4761 Number of Figures: 7 Number of Tables: 2Supplements: 1 supplementary information file + 1 excel file containing 2 supplementary data tables Abstract Background: 22q11.2 copy number variants (CNVs) are among the most highly penetrant genetic risk variants for developmental neuropsychiatric disorders such as schizophrenia (SCZ) and autism spectrum disorder (ASD). However, the specific mechanisms through which they confer risk remain unclear.Methods: Using a functional g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…The foregoing suggests a model in which genetic risk for schizophrenia operates not only on the formation and maintenance of synaptic networks during brain development, but also through direct effects on synaptic function and plasticity in the adult brain. This is supported by a recent study where pronounced enrichment of common genetic risk variation for schizophrenia was found in human brain gene co-expression modules involved in synaptic transmission and neuronal excitability that are maintained, or increased, in expression from birth into adulthood (91). Such a model is also consistent with key aspects of several other neurobiological theories of schizophrenia based on epidemiological, neuropathological, neuroimaging, neuropharmacological and cognitive findings (e.g.…”
Section: Synaptic Dysfunction As Both a Neurodevelopmental Antecedent And Ongoing Risk Mechanism For Schizophreniasupporting
confidence: 77%
“…The foregoing suggests a model in which genetic risk for schizophrenia operates not only on the formation and maintenance of synaptic networks during brain development, but also through direct effects on synaptic function and plasticity in the adult brain. This is supported by a recent study where pronounced enrichment of common genetic risk variation for schizophrenia was found in human brain gene co-expression modules involved in synaptic transmission and neuronal excitability that are maintained, or increased, in expression from birth into adulthood (91). Such a model is also consistent with key aspects of several other neurobiological theories of schizophrenia based on epidemiological, neuropathological, neuroimaging, neuropharmacological and cognitive findings (e.g.…”
Section: Synaptic Dysfunction As Both a Neurodevelopmental Antecedent And Ongoing Risk Mechanism For Schizophreniasupporting
confidence: 77%
“…Neurodevelopmental disorders, such as autism spectrum disorder, have been associated with defects in cortical circuits (Birnbaum and Weinberger, 2017;Del Pino et al, 2018;Ebert and Greenberg, 2013;Forrest et al, 2018;Forsyth et al, 2020;Gilman et al, 2011;Jabaudon, 2017;Mullins et al, 2016;Stoner et al, 2014; Writing Committee for the Attention-Deficit/Hyperactivity Disorder et al, 2021). Notably, a recent genetic study of autistic patients suggested that, during development, autism-associated genes are strongly enriched in maturing excitatory neurons, compared to immature progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Because neurodevelopmental disorders have been associated with cortical circuit dysfunction (Birnbaum and Weinberger, 2017;Del Pino et al, 2018;Ebert and Greenberg, 2013;Forrest et al, 2018;Forsyth et al, 2020;Gilman et al, 2011;Jabaudon, 2017;Mullins et al, 2016;Stoner et al, 2014), we analyzed the expression of neurodevelopmental disease-associated genes in embryonic layer 5 pyramidal neurons and compared this with expression in adult layer 5 pyramidal neurons (Tasic et al, 2018). A number of genes associated with schizophrenia (Lee et al, 2019;Ripke et al, 2014) and autism spectrum disorder (Abrahams et al, 2013) were expressed across all three embryonic types of Rbp4-Cre cells (Fig.…”
Section: Cell Type Specific Perturbation Of Autism-associated Genes R...mentioning
confidence: 99%
“…Interestingly, CNVs at many of these specific loci have pleiotropic effects, as they are also associated with broader neurodevelopmental disorders such as autism spectrum disorder (ASD) and intellectual disability (ID) 47,51,52 . Similar to common variants associated with schizophrenia, as well as other rare and de novo variants, schizophrenia-associated CNVs disproportionately affect neuronal and synaptic gene-sets 53 , including components of the postsynaptic density, and NMDAR and Arc complexes, 47,54 , and sets of genes that are involved in excitatory and inhibitory neurotransmission 55 .…”
Section: Overview Of Genetic Studies Of Aosmentioning
confidence: 99%